2021
DOI: 10.1108/jhti-01-2021-0021
|View full text |Cite
|
Sign up to set email alerts
|

When artificial intelligence meets the hospitality and tourism industry: an assessment framework to inform theory and management

Abstract: PurposeThis study reviews existing research and current applications of artificial intelligence (AI) in the hospitality and tourism industry. It further proposes a new evaluation framework to inform the susceptibility of AI adoptions.Design/methodology/approachThis is a synthesis and evaluation study that qualitatively summarizes and presents findings on AI applications in the hospitality and tourism industry. Current AI applications are rated using a seven-dimensional framework based on Rogers' (2003) diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 34 publications
0
46
0
Order By: Relevance
“…Ahani et al [64] reported similar results for SMEs' social customer relationship management adoption intention. In the context of AI, the technology's relative advantage for businesses has proven a key factor affecting its adoption [65][66][67]. Based on the above studies, we expect that SMEs that perceive advantages in adopting AI chatbots will be more likely to adopt such chatbots.…”
Section: Technological Factorsmentioning
confidence: 97%
“…Ahani et al [64] reported similar results for SMEs' social customer relationship management adoption intention. In the context of AI, the technology's relative advantage for businesses has proven a key factor affecting its adoption [65][66][67]. Based on the above studies, we expect that SMEs that perceive advantages in adopting AI chatbots will be more likely to adopt such chatbots.…”
Section: Technological Factorsmentioning
confidence: 97%
“…The advancement of emerging ICT technologies (information communication technology) has made significant impact on innovation and knowledge transfer in enterprises, including tourism enterprises. Huang et al (2021) researched qualitatively AI applications in the tourism and hospitality, and diffusion of innovations. They concluded that AI adoption susceptibility in this industry are varied depending on the type of AI.…”
Section: Knowledge and Innovationmentioning
confidence: 99%
“…RPA, in contrast to physical robots, refers to the software on which virtual bots run. RPA is a visual drag-and-drop system that automates tasks such as sending invoices, providing customers with refunds, and responding to clients in a consistent manner (Huang et al, 2021). Pure RPA is incredibly effective, but it only follows instructions from users or programmers, whereas AI can be self-learning.…”
Section: Robotization and Service Automatization In The Hotel Sectormentioning
confidence: 99%